2006
DOI: 10.1113/jphysiol.2006.110627
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cerebrovascular function on the hypercapnic ventilatory response in healthy humans

Abstract: An important determinant of [H(+)] in the environment of the central chemoreceptors is cerebral blood flow. Accordingly we hypothesized that a reduction of brain perfusion or a reduced cerebrovascular reactivity to CO(2) would lead to hyperventilation and an increased ventilatory responsiveness to CO(2). We used oral indomethacin to reduce the cerebrovascular reactivity to CO(2) and tested the steady-state hypercapnic ventilatory response to CO(2) in nine normal awake human subjects under normoxia and hyperoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
177
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(196 citation statements)
references
References 65 publications
17
177
1
1
Order By: Relevance
“…Plasma levels of Indo were not taken, and it is possible that absorption times resulted in different plasma levels. However, we used a typical drug wash-in period, similar to a previous study (49). In addition, we did not use a placebo-controlled double-blinded study design; instead, each subject was used as his or her own control, and young adults (where only slight changes were noted) served as a control group for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of Indo were not taken, and it is possible that absorption times resulted in different plasma levels. However, we used a typical drug wash-in period, similar to a previous study (49). In addition, we did not use a placebo-controlled double-blinded study design; instead, each subject was used as his or her own control, and young adults (where only slight changes were noted) served as a control group for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The engineering concept of "loop gain" has been around since the 1980s in the respiratory control literature as a key cause of CSA [ 16 ]. More recently, alterations of cerebral blood fl ow have been proposed as a potential key factor in CSA [ 35 ] (see Fig. 19.1 ).…”
Section: Mechanismsmentioning
confidence: 98%
“…This is contrary to what we observed in patients, as the cerebrovascular response was blunted. In healthy individuals, XIE et al [27] showed that decreased cerebrovascular responsiveness to CO 2 stimulates the ventilatory response, suggesting that cerebrovascular sensitivity to CO 2 has great influence on the V9E responsiveness of the central chemoreceptors. It is possible that the mechanisms involved in the control of breathing and cerebrovascular regulation in COPD patients are independently altered (i.e.…”
Section: Physiological Response To Hypercapniamentioning
confidence: 99%